Logic Model Evaluation of Teaching Assistance in Islamic Teacher Education - Aminulloh; Padmadewi, Ni Nyoman; Utami, IGA. Lokita Purnamika; Yanyan, Bi; Jiaxin, Liu (Faculty of Educational Sciences, UIN (State Islamic University) Syarif Hidayatullah Jakarta, 2025)
Abstract Experiential learning through teaching assistance programs plays a vital role in the professional development of prospective teachers, especially within Islamic higher education contexts. However, few evaluation frameworks comprehensively explore the relationships among program components and their direct effects on educational outcomes. This study employs the Logic Model framework to systematically analyze the Teaching Assistance Program at the Faculty of Tarbiyah and Teacher Training, UIN Kiai Haji Achmad Siddiq Jember, during the 2024–2025 academic year. By mapping inputs, activities, outputs, outcomes, and long-term impacts, the study offers an integrated evaluation of how teaching assistance fosters professional competencies and instructional quality development. Utilizing a qualitative approach, including semi-structured interviews, focus groups, and document analysis, with participation from 114 sixth-semester students across nine study programs, the research uncovers the critical influence of structured mentorship and contextual adaptation across disciplines. It also reveals challenges such as inconsistent supervision and lack of standardized practices. This study contributes to advancing program evaluation methodologies in Islamic teacher education by demonstrating the utility of the Logic Model to reveal program dynamics and inform strategic enhancement of teaching assistance frameworks. The findings carry significant implications for promoting equitable, coherent, and sustainable teacher preparation programs within diverse institutional environments. Abstrak Pembelajaran berbasis pengalaman melalui program bantuan pengajaran memegang peranan penting dalam pengembangan profesional calon guru, khususnya dalam konteks pendidikan tinggi Islam. Namun, sedikit kerangka evaluasi yang secara komprehensif mengeksplorasi hubungan antar komponen program dan dampak langsungnya terhadap hasil pendidikan. Studi ini menggunakan kerangka Kerja Logic Model untuk secara sistematis menganalisis Program Bantuan Pengajaran di Fakultas Tarbiyah dan Ilmu Keguruan, UIN Kiai Haji Achmad Siddiq Jember, selama tahun akademik 2024–2025. Dengan memetakan input, aktivitas, keluaran, hasil, dan dampak jangka panjang, penelitian ini menawarkan evaluasi terpadu tentang bagaimana bantuan pengajaran mendorong kompetensi profesional dan pengembangan kualitas instruksional. Menggunakan pendekatan kualitatif yang meliputi wawancara semi-terstruktur, diskusi kelompok fokus, dan analisis dokumen, dengan partisipasi 114 mahasiswa semester enam dari sembilan program studi, penelitian ini mengungkap pengaruh penting pendampingan terstruktur dan adaptasi kontekstual lintas disiplin. Studi ini juga mengidentifikasi tantangan seperti pengawasan yang tidak konsisten dan kurangnya praktik standar. Penelitian ini berkontribusi pada pengembangan metodologi evaluasi program dalam pendidikan guru Islam dengan menunjukkan kegunaan Logic Model untuk mengungkap dinamika program dan memberikan informasi untuk peningkatan strategis kerangka bantuan pengajaran. Temuan penelitian memiliki implikasi signifikan untuk mendorong program persiapan guru yang adil, koheren, dan berkelanjutan dalam lingkungan institusional yang beragam.